OPTIMALISASI LAYANAN INFORMASI JADWAL DOKTER SEBAGAI SOLUSI TERHADAP KETIDAKPUASAN PASIEN DI RUMAH SAKIT YUKUM MEDICAL CENTRE - Putra, Yogi Catur; Mayasari, Fitri; CATUR, Fikri Haikal Zidki; Mayasari, Ratna Juwita; CATUR, Muhammad Azzam Fauzan; Mayasari, Devika Anggraini; Mayasari, Anadita Salsabela; CATUR, Sofia Rahma Aqila; Khoiriyah, Safina Animatul; Mayasari, Septi Usmana Laupita (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: Patient dissatisfaction with changes in doctor's schedules is a crucial problem in health services. One crucial aspect of service is the transparency of information, especially regarding the doctor's practice schedule. Because the uncertainty of this information makes patients feel dissatisfied and has an impact on the quality of hospital services. Method: This study uses a quantitative approach with the Importance Performance Analysis (IPA) method to measure patient satisfaction and a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to formulate strategies for improving doctor's schedule information services. Results: The analysis shows that unclear information and delays in updating doctor's schedules are the main aspects that need to be improved immediately. Conclusion: Optimization of an integrated application-based doctor's schedule information system is recommended as an innovative solution to improve patient satisfaction, health worker work efficiency, and strengthen the image of excellent hospital service.